Production of bioplastics based on plantain peel starch and chitosan with sorbitol plasticizer - Eka Saputri; Halim Daulay, Abdul; Masthura, Masthura (Universitas Negeri Medan, 2026)
Bioplastic is an alternative to conventional plastic. Bioplastic is made from natural polymer materials such as starch. In its manufacture, it is necessary to add other materials, namely chitosan as an adhesive and plasticizer as a plasticizer. The purpose of this study was to determine the optimum composition of bioplastic material so that it has physical properties, mechanical properties and biodegradability that meet applicable bioplastic standards. This study used starch extracted from plantain peels of 4 g and varied the addition of chitosan (2, 3, 4, 5, g) with the addition of sorbitol of 6 ml. The characterization carried out included water absorption tests, biodegradation tests, tensile strength tests, elongation tests, and FTIR (Fourier Transform Infra Red) tests. The resulting characterization data for the manufacture of bioplastics included water absorption test values of 14-79%, biodegradation values of 56-80%, tensile strength tests of 0.26-0.87 MPa, and elongation percentage tests of 6.5-25.5%. Meanwhile, the results of the FTIR test obtained the same group from the constituent components, namely the functional groups OH, CH, NH, and CO. The data from the characterization of bioplastics with the optimum composition were found in sample D because the water absorption test value of 14% had met ASTM D570-98, the ability to degrade was 56%, the tensile strength value was 0.87 MPa, and the percent elongation value was 25.5% had met ASTM D882-12.